Detection and quantification of small concentrations of moxifloxacin using surface‐enhanced Raman spectroscopy in a Kretschmann configuration. (5th May 2021) - Mohaghegh, Faezeh; Mazaheri Tehrani, Alireza; Rana, Debkumar; Winterhalter, Mathias; Materny, Arnulf
Abstract: A relatively simple experimental procedure is proposed for the simultaneous detection and quantitative assessment of moxifloxacin (Moxi) as an example for an antibiotic using surface‐enhanced Raman spectroscopy (SERS) performed in a Kretschmann configuration (KC). The example of Moxi shows the advantage of this approach, such as high sensitivity and relatively simple experimental procedure. The Moxi was reliably detected at levels of 100 nM using excitation laser powers as low as a few milliwatts. We also demonstrate that in the KC, the direct coupling between the electronic systems of analyte molecules and metal substrate contributing to the chemical enhancement mechanism in SERS plays a major role. For this, we have performed simulations based on density functional theory (DFT). The line profile of the SERS spectra can be explained by the direct coupling of molecular sites to the metal. This adds to the molecular specificity of SERS when using the KC. Abstract : Detection of moxifloxacin down to 100 nM in aqueous solution by surface‐enhanced Raman spectroscopy (SERS) using a highly reproducible Kretschmann configuration. Experimental and DFT investigations are presented pointing to a major contribution of the chemical SERS mechanism when using a well‐defined flat silver layer on the prism.